Preparation method of high-first-effect three-dimensional SnS2 graphene lithium ion battery negative electrode material with adjustable cavity
Through the template-guided self-assembly strategy and electrostatic combination, a three-dimensional SnS2 graphene composite material with adjustable cavity was prepared, which solved the problems of tin disulfide nanosheet agglomeration and disordered growth of SEI films, significantly improving the cyclic stability and reversible specific capacity of the material.
Patent Information
- Application Number
- CN202510055319.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-14
AI Technical Summary
In the prior art, tin disulfide is prone to agglomeration of nanosheets when growing in situ on the graphene surface, and the SEI film grows disorderly, resulting in structural instability during the cycle.
Through the template-guided self-assembly strategy, using PS spheres as templates, combined with electrostatic binding, the inorganic metal salt is uniformly attached to the surface of graphene oxide. After calcination reaction, a three-dimensional SnS2 graphene composite material with an adjustable cavity was finally obtained.
In situ growth of SnS2 in three-dimensional graphene structure is achieved, nanosheet agglomeration is avoided, the controlled growth of SEI film is promoted, and the circulation stability and reversible specific capacity of the material are significantly improved.
Smart Images

Figure CN119852367A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of energy storage materials, and specifically develops a method for preparing a high first-efficiency three-dimensional SnS2 graphene lithium-ion battery negative electrode material with adjustable cavity. The present invention first prepares PS@SnO2@GO through a template-guided self-assembly strategy, then adds thiourea for calcination reaction, and finally obtains a high first-efficiency three-dimensional SnS2 graphene (3D-SnS2@rGO) composite material with adjustable cavity. The material exhibits excellent cycle stability and high reversible specific capacity at different current densities. This new preparation method of tin disulfide graphene negative electrode material with adjustable cavity lays the foundation for the application of high-performance transition metal sulfide-based negative electrode materials. Background Art
[0002] Driven by the growing market demand for new energy vehicles, electronic products, and aerospace power sources, it is particularly important to develop advanced energy storage systems with high energy, long life, and good cycle stability. As the negative electrode material of commercial lithium-ion batteries, graphite has the advantages of stable chemical properties, low charge and discharge potential platform, and no obvious volume expansion. However, the graphite negative electrode has a low theoretical specific capacity (372mAh g -1 ), which cannot meet the pursuit of more powerful electronic devices. In this regard, SnS2 and MoS2, as typical tin-based and molybdenum-based compound materials, have lower lithium insertion voltage and higher theoretical capacity, and are expected to become negative electrode materials for LIB. In addition, compared with oxides, metal sulfides have higher electrochemical reaction activity and reversibility due to weaker metal-sulfur bonds. However, low electrical conductivity and slow reaction kinetics make it difficult to fully utilize their capacity, resulting in poor rate performance. In addition, the high volume expansion rate of metal sulfides leads to electrode powdering during the lithium insertion and extraction process. Using PS as a substrate and compounding with graphene is an effective method to solve the problem of metal sulfide anodes. The addition of PS spheres and graphene can greatly improve the electrical conductivity and ion transfer efficiency of the material, while increasing the structural stability of the material.
[0003] In the traditional synthesis method, SnS2 is mainly grown in situ on the surface of two-dimensional graphene nanosheets. For example, patent CN106129378A proposes to grow SnS2 in situ on the surface of graphene through a hydrothermal process. However, this method can easily cause the agglomeration of SnS2 nanosheets. At the same time, SnS2 is directly exposed to the electrolyte environment, resulting in disordered growth of SEI film and the occurrence of shuttle effect. Summary of the invention
[0004] The present invention aims to solve the problems of disordered growth of SEI film on the surface of tin disulfide and stacking of graphene sheets in the current traditional preparation method, which makes it difficult to maintain a stable structure during the cycle. The present invention provides a preparation method for a three-dimensional SnS2 graphene lithium-ion battery negative electrode material with high first efficiency and adjustable cavity. The invention uses PS spheres as templates, obtains a mixed dispersion of metal salts and graphene oxide that are evenly mixed with PS spheres through electrostatic bonding, and finally obtains a three-dimensional graphene structure with an internally anchored SnS2 cavity after a one-step calcination. The present invention does not require a removal process, and the lithium-ion battery assembled from the composite material has a high initial efficiency of 0.2A g -1 The first discharge capacity is as high as 1633mA hg -1 After 100 cycles, the reversible specific capacity reaches 1215 mA hg -1 The first coulombic efficiency is as high as 88%. It shows excellent cycle stability and high reversible specific capacity at low current density.
[0005] The technical solution of the present invention is:
[0006] A method for preparing a high first-efficiency three-dimensional SnS2 graphene lithium-ion battery negative electrode material with an adjustable cavity, the method comprising the following steps:
[0007] (1) dissolving an inorganic metal salt in deionized water, referred to as solution A, and then adding NaOH to solution A under stirring. When the solution changes from clear to turbid, and then becomes clear again, solution B is obtained;
[0008] Wherein, 0.1-2.0 g of inorganic metal salt and 500-800 mg of NaOH are added to every 10-100 mL of deionized water;
[0009] The inorganic metal salt is tin tetrachloride pentahydrate (SnCl4·5H2O) or ammonium molybdate ((NH4)2MoO4);
[0010] (2) adding solution B dropwise into the PS ball dispersion to form a metal salt@PS dispersion solution;
[0011] The mass concentration of PS spherical solution is 0.1~5mg mL -1 ; The volume ratio of PS ball dispersion and solution B is 4-12:1;
[0012] When the metal salt in step (1) is tin tetrachloride pentahydrate, a surfactant polyvinyl pyrrolidone (PVP) is also added to the PS sphere dispersion and mixed for 1 to 5 hours, with the mass ratio of PS sphere solution to PVP being 1:0.1 to 2;
[0013] The particle size of PS spheres is 80 to 570 nm;
[0014] (3) adding hydrochloric acid to the metal salt@PS dispersion solution to make the pH value neutral, thereby obtaining a metal oxide@PS dispersion solution;
[0015] The concentration of hydrochloric acid is 0.1 to 2 mol L -1 ;
[0016] (4) Preparation of metal oxide@PS@rGO compounds:
[0017] The GO dispersion is added to the metal oxide@PS dispersion and stirred for 4 to 8 hours, then sodium ascorbate is added and stirred at 80 to 120° C. for 0.1 to 2 hours; then centrifuged, washed and freeze-dried to obtain a metal oxide@PS@rGO compound;
[0018] The mass concentration of GO dispersion is 0.1-2 mg mL -1 , add 300-450 mg sodium ascorbate to every 200-250 ml of metal oxide@PS dispersion, and the volume ratio of GO dispersion to metal oxide@PS dispersion is 1:10-20;
[0019] (5) High temperature vulcanization:
[0020] The thiourea and the metal oxide @PS@rGO are placed in a glass container in sequence, the porcelain boat containing the thiourea is placed upstream of the container, and the solid product metal oxide @PS@rGO is placed downstream of the container, and then the glass container is placed in a tube furnace, and after heat treatment at 300 to 500° C. for 1 to 5 hours under the protection of an inert atmosphere, a high first-efficiency three-dimensional SnS2 graphene lithium-ion battery negative electrode material with an adjustable cavity is obtained;
[0021] Wherein, 2 to 4 g of thiourea is added to every 0.20 to 1.00 g of the metal oxide@PS@rGO compound obtained from the inorganic metal;
[0022] The graphene oxide in step (4) is graphene oxide prepared by the improved Hummers method.
[0023] The inert gas is argon;
[0024] The size of the "cavity size" is 105 to 596 nm;
[0025] Application of a high first-efficiency three-dimensional SnS2 graphene lithium-ion battery negative electrode material with adjustable cavity prepared by the method, used as a negative electrode plate of a lithium-ion battery;
[0026] The method comprises the following steps: mixing the electrode material obtained in (5) with conductive carbon and a binder at a mass ratio of 8:1:1 to obtain a mixed material, adding deionized water, and stirring at room temperature for 6 to 24 hours; after stirring, coating the obtained suspension evenly on a copper foil, with a coating amount per unit area of 0.5 to 2 mg cm -2 , and vacuum drying at 80-120° C. for 10-20 h to obtain a negative electrode sheet for a lithium ion battery;
[0027] Add 50-250 mg of mixed material per 600-1000 μL of deionized water;
[0028] The binder is sodium carboxymethyl cellulose and the conductive carbon is Super P.
[0029] The positive electrode of the lithium-ion battery is a metal lithium sheet, the diaphragm is a glass fiber membrane, and the electrolyte is 1.0 mol L - 1 Solution of LiPF6 in a mixture of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC) and ethylene carbonate (EC) in a volume ratio of 1:1:1.
[0030] The essential features of the present invention are:
[0031] In previous invention patents, the preparation of metal sulfide and graphene composite materials usually involves the removal of impurities, the synthesis process is relatively cumbersome, and the traditional one-pot hydrothermal method combined with high-temperature calcination is difficult to effectively control the nanostructure of the composite material, which makes it difficult to fully exert the advantages of the metal sulfide negative electrode material itself, and the volume expansion problem during the lithium ion extraction / insertion process also needs to be solved urgently.
[0032] The present invention uses easily decomposable inorganic metal salts and thiourea as metal sources and sulfur sources, and size-adjustable PS spheres and graphene nanosheets as conductive substrates. Through the electrostatic binding of metal ions and graphene oxide (GO) nanosheets, the inorganic metal salts uniformly attached to the surface of the PS spheres are adsorbed as "seeds" on the surface of graphene oxide. After centrifugation, washing and freeze-drying, the metal salts can be anchored on the GO nanosheets, and finally a composite material of a three-dimensional SnS2 graphene heterostructure with an adjustable cavity is obtained through high-temperature vulcanization. The inventor has found through research that the composite material designed and synthesized by the self-assembly method of a variety of conductive substrates, with PS spheres as the basic unit, can provide a large number of electrochemical reaction active sites; at the same time, the good stress tolerance of the PS sphere cavity can effectively alleviate the volume expansion problem during its charge and discharge process, and further increase the structural stability of the material; and this directional and close arrangement can provide a multi-path high-speed transmission channel for lithium ion conduction. In addition, the nitrogen and sulfur elements produced after the decomposition of thiourea will be doped into the metal salt lattice and the carbon skeleton of the graphene sheet, which can greatly improve the conductivity, accelerate the charge transfer, reduce the lithium ion migration barrier, and further improve the electrochemical performance of the material.
[0033] The beneficial effects of the present invention are:
[0034] (1) The present invention introduces PS balls as templates to transform two-dimensional graphene into a three-dimensional network structure, and adsorbs metal salts uniformly attached to the surface of the PS balls onto GO nanosheets through electrostatic action, so that SnS2 grows in the cavity of the PS balls, thereby obtaining a three-dimensional graphene hybrid material different from traditional two-dimensional materials;
[0035] (2) The present invention utilizes electrostatic adsorption to uniformly attach metal salt ions to the PS spheres with positive charges on the surface, and adjusts the pH value to convert the metal salt ions into hydroxides;
[0036] (3) The PS spheres coated with tin hydroxide are evenly attached to the surface of the negatively charged graphene oxide sheet. The operation process is simple and the experimental conditions are mild.
[0037] (4) Through high-temperature sulfurization and calcination, the in-situ growth of metal sulfide nanoparticles in the three-dimensional network graphene was achieved. The 3D-SnS2@rGO-310 negative electrode material prepared under the optimal conditions in this experiment has a high conductivity at 0.2A g -1 The reversible specific capacity after 100 cycles reaches 1215 mA hg -1 , while at 1A g -1 After 1000 cycles of charge and discharge at the same current density, it can still maintain 910mA hg -1 The reversible specific capacity;
[0038] (5) The 3D-MoS2@rGO-310 negative electrode material prepared under the optimal conditions in this experiment has a high conductivity at 0.2A g -1 The reversible specific capacity after 100 cycles reaches 940 mA hg -1 ;
[0039] (6) The present invention can also replace different metal salt precursors to achieve the construction of three-dimensional graphene hybrid materials with adjustable cavities. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 is a scanning electron microscope image of the 3D-SnS2@rGO-310 composite material in Example 1;
[0041] Figure 2 is the X-ray diffraction pattern of the 3D-SnS2@rGO-310 composite material in Example 1;
[0042] Figure 3 The 3D-SnS2@rGO-310 composite material in Example 1 was -1 Cycling performance diagram under current density;
[0043] Figure 4 The 3D-SnS2@rGO-310 composite material in Example 1 at 1A g -1 Cycling performance diagram under current density;
[0044] Figure 5 This is the rate performance diagram of the 3D-SnS2@rGO-310 composite material in Example 1;
[0045] Figure 6 The 3D-SnS2@rGO-570 composite material in Example 2 was -1 Cycling performance diagram under current density;
[0046] Figure 7 The 3D-SnS2@rGO-80 composite material in Example 3 was -1 Cycling performance diagram under current density;
[0047] Figure 8 The SnS2@rGO composite material in Example 4 at 0.2A g -1 Cycling performance diagram under current density;
[0048] Fig. 9 is a scanning electron microscope image of the 3D-MoS2@rGO-310 composite material in Example 5;
[0049] Fig.10This is the XRD test curve of the 3D-MoS2@rGO-310 composite material in Example 5;
[0050] Fig.11 The 3D-MoS2@rGO-310 composite material in Example 5 was -1 Cycling performance diagram under current density; DETAILED DESCRIPTION
[0051] In the present invention, PS spheres are introduced into the composite system as templates to construct a three-dimensional graphene network with adjustable cavities, so that SnS2 grows in the spherical cavities. The three-dimensional graphene network avoids the stacking phenomenon caused by van der Waals forces between the original two-dimensional sheets. At the same time, under the protection of the spherical cavities, SnS2 avoids direct contact with the electrolyte and promotes the controllable growth of the SEI film.
[0052] During the preparation, the inorganic metal salt is first prepared into an aqueous solution, and NaOH solution is added to obtain a uniform inorganic metal salt solution, which is then mixed with a PS spherical solution uniformly mixed with PVP to form a metal salt @PS dispersion, which is then mixed evenly with a graphene oxide dispersion and sodium ascorbate is added and stirred evenly. The dispersion is then centrifuged, washed, and freeze-dried to form a metal hydroxide @PS @rGO compound. After high-temperature sulfurization, a composite material of a three-dimensional SnS2 graphene heterostructure with an adjustable cavity is finally obtained. The material exhibits a high reversible specific capacity and excellent rate performance. This new preparation method of a metal sulfide and graphene heterostructure negative electrode material lays the foundation for the application of high-performance metal sulfide negative electrode materials in the field of energy storage.
[0053] Example 1
[0054] Add 0.701 g of tin tetrachloride pentahydrate to 20 mL of deionized water and stir to obtain Sn 4+ solution, recorded as solution A; gradually add solid NaOH to solution A, the solution changes from clear to turbid, until the solution becomes clear again (about 650 mg of NaOH), Sn 4+ Converted to SnO3 2- , recorded as solution B. Subsequently, a polystyrene (PS) spherical solution (200 mL, 1 mg mL -1 ) Literature number: Adv.Funct.Mater.2017,27,1702807, mixed with 40mg PVP for 2 hours, and gradually added all the solution B prepared above. Under the action of electrostatic force, the two combined to form SnO3 2- @PS dispersion. Then add 0.5mol L -1HCL, make the pH value neutral, stir the solution for 2 hours until it is mixed evenly, so that SnO3 2- @PS was converted into SnO2@PS dispersion. Graphene oxide (GO-based on the improved Hummers method, literature number: Journal of Alloys and Compounds 862(2021)158472) dispersion (15 mL, 2 mg mL -1 ) was added to the SnO2@PS dispersion prepared above and stirred for 6 hours. Then, 0.396 g of sodium ascorbate was added and stirring was continued at 90°C for 2 hours. The above dispersion was centrifuged, washed and freeze-dried to obtain a Sn(OH)4@PS@rGO solid product; 3 g of thiourea and all the solid products Sn(OH)4@PS@rGO prepared above were placed in a specific glass container in sequence, the porcelain boat containing thiourea was placed upstream of the container, and all the Sn(OH)4@PS@rGO solid products were placed downstream of the container, and then the glass container was placed in a tubular furnace and heated in an argon atmosphere (120 mL min from upstream to downstream). -1 The product was heat treated at 500℃ for 3h under the protection of a flow rate purge (with a heating rate of 10℃ / min). The cavity size after calcination was 342nm, and a three-dimensional SnS2@graphene composite material with adjustable cavity (labeled as 3D-SnS2@rGO-310) was obtained.
[0055] The obtained 3D-SnS2@rGO-310 composite material was uniformly mixed with conductive carbon (Super P) and binder (sodium carboxymethyl cellulose) at a mass ratio of 8:1:1 (total amount of 125 mg) to obtain a SnS2@graphene mixed material, and 800 μL of deionized water was added and stirred at room temperature for 12 hours; after stirring, the obtained SnS2@graphene mixed material suspension was uniformly coated on copper foil (the coating amount on each square centimeter of copper foil was about 1 mg), and vacuum dried at 100°C for 12 hours; the obtained electrode sheet was cut into a disc with a diameter of 12 mm using a manual slicer to obtain a negative electrode sheet. In this embodiment, the battery adopts a standard half-cell configuration, the battery shell is a CR2025 stainless steel button battery, a lithium sheet is used as the counter electrode, Celgard 2500 is used as a diaphragm, and the electrolyte is a mixed solution of 1M LiPF6 ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) (volume ratio 1:1:1). The test voltage range is 0.01~3V, and the test current is 0.2A g -1 The test adopts LAND CT2001A battery test system.
[0056] Figure 1This is a scanning electron microscope image of the 3D-SnS2@rGO-310 composite material in Example 1. The image shows that the PS spheres are uniformly attached to the graphene, and the tin disulfide nanosheets grow in the spherical cavity without obvious agglomeration. During the whole process, the PS spheres with tin oxide on the outside are embedded in the graphene during stirring. In the subsequent calcination process, the PS spheres are removed and the tin oxide is converted into tin disulfide. The final cavity size includes the thickness of SnS2. In this example, the PS sphere size is 310nm and the cavity size is 342nm.
[0057] Figure 2 This is the XRD test curve of the 3D-SnS2@rGO-310 composite material in Example 1, which shows a tin disulfide crystal structure. No obvious graphene characteristic diffraction peak is observed in the figure. This is because the diffraction peak of tin disulfide is strong, thus obscuring the peak of graphene.
[0058] Figure 3 The 3D-SnS2@rGO-310 composite material in Example 1 was -1 Cyclic performance diagram under current density. The discharge and charge specific capacities of the composite material in the first cycle were 1633 and 1439 mA h g -1 The first coulombic efficiency reached 88%, and the reversible specific capacity after 100 cycles reached 1215mA hg -1 , the Coulombic efficiency is close to 100%.
[0059] Figure 4 The 3D-SnS2@rGO-310 composite material has a -1 Cycling performance diagram under current density. The reversible specific capacity of the composite material after 1000 cycles reaches 910mA hg -1 , the Coulombic efficiency is close to 100%.
[0060] Figure 5 The rate performance diagram of 3D-SnS2@rGO-310 composite material. -1 and 5Ag -1 The reversible specific capacity at the current density of 1.177 W / m and 1.22 W / m respectively reached 1132 mAh g -1 and 977mA hg -1 , indicating its excellent rate performance.
[0061] Example 2
[0062] The steps are the same as those in Example 1, except that the size of the PS balls (570 nm) and the cavity size (596 nm) are changed, and other conditions remain unchanged. The final composite material is recorded as 3D-SnS2@rGO-570.
[0063] Figure 6 The 3D-SnS2@rGO-570 composite material has a -1 Cyclic performance diagram under current density. The discharge and charge specific capacities of the composite material in the first cycle were 1257 and 1024 mA h g -1 After 100 cycles, the reversible specific capacity reaches 945 mA hg -1 .
[0064] Example 3
[0065] The steps are the same as those in Example 1, except that the size of the PS balls (80 nm) and the cavity size are changed to 105 nm. Other conditions remain unchanged, and the final composite material is recorded as 3D-SnS2@rGO-80.
[0066] Figure 7 The 3D-SnS2@rGO-80 composite material has a -1 Cyclic performance diagram under current density. The discharge and charge specific capacities of the composite material in the first cycle were 1294 and 1030 mA h g -1 After 100 cycles, the reversible specific capacity reaches 898 mA hg -1 .
[0067] Example 4
[0068] The steps are the same as those in Example 1, except that the PS sphere solution does not need to be added, and other conditions remain unchanged. The final composite material is recorded as SnS2@rGO.
[0069] Figure 8 The SnS2@rGO composite material has a -1 Cyclic performance diagram under current density. The discharge and charge specific capacities of the composite material in the first cycle were 1578 and 1122 mA h g -1 After 100 cycles, the reversible specific capacity reaches 745 mA hg -1 , which shows that compared with the two-dimensional graphene structure, the introduction of PS spheres as templates to construct a three-dimensional graphene network with cavities realizes the in situ growth of SnS2 nanoparticles in the cavities. The three-dimensional conductive network provides more channels for lithium ion electron transmission. At the same time, the cavity effectively alleviates the volume expansion of SnS2 during the cycle. Based on the above structural advantages, the negative electrode material exhibits extremely high first efficiency and excellent reversible specific capacity.
[0070] Example 5
[0071] The steps are the same as those in Example 1, except that the tin tetrachloride pentahydrate added to dispersion A is replaced with ammonium molybdate, and the added mass is 0.392 g. When mixing with the PS spherical solution, there is no need to add the surfactant PVP. Other conditions remain unchanged. The final composite material is recorded as 3D-MoS2@rGO-310.
[0072] Fig. 9 This is a scanning electron microscope image of the 3D-MoS2@rGO-310 composite material, in which MoS2 nanoparticles grown on the graphene surface can be observed.
[0073] Fig.10 This is the XRD test curve of 3D-MoS2@rGO-310 composite material.
[0074] Fig.11 Figure 3 shows the cycling performance of the 3D-MoS2@rGO-310 composite material. The discharge and charge specific capacities of the composite material in the first cycle were 1151 and 920 mA h g -1 After 100 cycles, the reversible specific capacity reaches 940 mA hg -1 , the Coulombic efficiency is close to 100%.
[0075] Matters not covered by the present invention are known technologies.
Claims
1. A method for preparing a three-dimensional SnS2 graphene lithium-ion battery negative electrode material with high initial efficiency and adjustable cavity, characterized in that: The method comprises the following steps: (1) dissolving an inorganic metal salt in deionized water, referred to as solution A, and then adding NaOH to solution A under stirring. When the solution changes from clear to turbid, and then becomes clear again, solution B is obtained; Wherein, 0.1-2.0 g of inorganic metal salt and 500-800 mg of NaOH are added to every 10-100 mL of deionized water; The inorganic metal salt is tin tetrachloride pentahydrate (SnCl4·5H2O) or ammonium molybdate ((NH4)2MoO4); (2) adding solution B dropwise into the PS ball dispersion to form a metal salt@PS dispersion solution; The mass concentration of PS spherical solution is 0.1~5mg mL -1 ; The volume ratio of PS ball dispersion and solution B is 4-12:1; When the metal salt in step (1) is tin tetrachloride pentahydrate, a surfactant polyvinyl pyrrolidone (PVP) is also added to the PS sphere dispersion and mixed for 1 to 5 hours, with the mass ratio of PS sphere solution to PVP being 1:0.1 to 2; (3) adding hydrochloric acid to the metal salt@PS dispersion solution to make the pH value neutral, thereby obtaining a metal oxide@PS dispersion solution; The concentration of hydrochloric acid is 0.1 to 2 mol L -1 ; (4) Preparation of metal oxide@PS@rGO compounds: The GO dispersion is added to the metal oxide@PS dispersion and stirred for 4 to 8 hours, then sodium ascorbate is added and stirred at 80 to 120° C. for 0.1 to 2 hours; then centrifuged, washed and freeze-dried to obtain a metal oxide@PS@rGO compound; The mass concentration of GO dispersion is 0.1-2 mg mL -1 , add 300-450 mg sodium ascorbate to every 200-250 ml of metal oxide@PS dispersion, and the volume ratio of GO dispersion to metal oxide@PS dispersion is 1:10-20; (5) High temperature vulcanization: The thiourea and the metal oxide @PS@rGO are placed in a glass container in sequence, the porcelain boat containing the thiourea is placed upstream of the container, and the solid product metal oxide @PS@rGO is placed downstream of the container, and then the glass container is placed in a tube furnace, and after heat treatment at 300 to 500° C. for 1 to 5 hours under the protection of an inert atmosphere, a high first-efficiency three-dimensional SnS2 graphene lithium-ion battery negative electrode material with an adjustable cavity is obtained; Among them, 2 to 4 g of thiourea is added to every 0.20 to 1.00 g of the metal oxide@PS@rGO compound obtained by the inorganic metal.
2. The method for preparing a high first-efficiency three-dimensional SnS2 graphene lithium-ion battery negative electrode material with adjustable cavity as claimed in claim 1, characterized in that: The graphene oxide in step (4) is graphene oxide prepared by the improved Hummers method.
3. The method for preparing a high first-efficiency three-dimensional SnS2 graphene lithium-ion battery negative electrode material with adjustable cavity as claimed in claim 1, characterized in that: The inert gas is argon.
4. The method for preparing a high first-efficiency three-dimensional SnS2 graphene lithium-ion battery negative electrode material with adjustable cavity as claimed in claim 1, characterized in that: The particle size of PS spheres is 80-570 nm; the cavity size is 105-596 nm.
5. Application of a high first-efficiency three-dimensional SnS2 graphene lithium-ion battery negative electrode material with adjustable cavity prepared by the method as claimed in claim 1, characterized in that it is used as a negative electrode sheet of a lithium-ion battery.
6. The use according to claim 5, characterized in that The following steps are involved: The electrode material obtained in (5) is mixed with conductive carbon and a binder at a mass ratio of 8:1:1 to obtain a mixed material, deionized water is added, and the mixture is stirred at room temperature for 6 to 24 hours. After the stirring, the obtained suspension is evenly coated on a copper foil, and the coating amount per unit area is 0.5 to 2 mg cm -2 , and vacuum drying at 80-120° C. for 10-20 h to obtain a negative electrode sheet for a lithium ion battery; Add 50-250 mg of mixed material per 600-1000 μL of deionized water; The binder is sodium carboxymethyl cellulose and the conductive carbon is Super P; The positive electrode of the lithium-ion battery is a metal lithium sheet, the diaphragm is a glass fiber membrane, and the electrolyte is 1.0 mol L -1 Solution of LiPF6 in a mixture of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC) and ethylene carbonate (EC) in a volume ratio of 1:1:1.
Citation Information
Patent Citations
Composite material with hollow graphene spheres loaded with nanometer tin disulfide and method for preparing composite material
CN105621355A
Preparation method for stannic disulfide / graphene nanocomposite, negative electrode of lithium ion battery, and lithium ion battery
CN106129378A
Preparation method of 3D honeycomb-like reduced grapheme oxide tin disulfide compound
CN107134574A
Preparation method of novel graphene / SnS2 composite material lithium ion battery anode material
CN110010870A
SnS2 / rGO modified sulfur positive electrode material and preparation method and application thereof
CN111106346A